Intradural paragangliomas in the cauda equina region: a case report and literature review - Ma, Jiang-Chun; Shi, Xiao-Yong; Sun, Hu; Lei, Huan; Tang, Zhu-Xiao (Frontiers in Oncology, 2025)
IntroductionCauda Equina Paragangliomas (CEPs) are rare neuroendocrine tumors with an atypical clinical profile. They pose diagnostic and therapeutic challenges due to their varied manifestations and low incidence. This case report aims to contribute to the limited literature on CEPs by detailing the presentation, diagnosis, and surgical management of a new case.Case reportA 51-year-old female presented with a 20-day history of worsening lumbago and urinary dysfunction. MRI scans revealed a 2cm mass at the L1 vertebral level, leading to the diagnosis of an intraspinal CEP. The patient underwent a successful surgical resection with intraoperative monitoring to manage hemodynamic changes. Postoperative care included hypertension management, and the patient was discharged after a three-week recovery period with a plan for long-term follow-up.ConclusionThe successful surgical resection of this CEP highlights the importance of precise preoperative imaging and a multidisciplinary approach to management. Despite the rarity of CEPs, this case underscores the feasibility of complete tumor removal and the necessity for long-term monitoring. The evolving landscape of diagnostic and therapeutic tools holds promise for improving outcomes in these rare tumors. Continued research and collaboration are vital for enhancing our understanding and treatment of CEPs.